Depressive self-focus bias following failure: an eye-tracking study among individuals with clinical depression - Monéger, Jean; Harika-Germaneau, Ghina; Jaafari, Nematollah; Doolub, Damien; Warck, Laura; Selimbegović, Leila; Chatard, Armand (Frontiers in Psychiatry, 2024)
Objective Depression is often characterized by a persistent sense of failure. Cognitive theories of depression suggest that depressed individuals may exhibit a maladaptive cognitive style, characterized by increased self-focus following personal failure. The validity of this proposition, however, is yet to be fully examined. This study aimed to identify the relation between symptoms in major depressive disorder and increased self-focus in failure situations. Methods This clinical study involved a cohort of 30 patients diagnosed with and treated for depression. We used an eye-tracking paradigm to observe and analyze gaze direction – indicative of either self-focus or self-avoidance – after remembering a significant failure event. Results Contrary to the maladaptive cognitive style hypothesis, a majority of the depressed participants demonstrated an inclination towards self-avoidance following failure. Nevertheless, approximately 30% of the patient group – those with the highest scores of guilt, punishment, and self-blame – displayed a self-focused attentional bias post-failure. Conclusions The presence of a maladaptive self-focusing style may be confined to severely depressed patients with high levels of guilt, punishment, and self-blame. These findings could have substantial clinical implications, as attention bias modification interventions could be particularly beneficial for this subgroup of patients.